COMPUTER BASED TEST (CBT) SEBAGAI ALTERNATIF INSTRUMEN EVALUASI PEMBELAJARAN - -, Evi Murniati - (Prosiding Seminar Pendidikan Ekonomi dan Bisnis, 2017)
ABSTRACT This study to know the feasibility of using the learning evaluation instruments Computer Based Test (CBT) and test the effectiveness of the instrument to improve Kearsipan learning outcomes in vocational school of Karanganyar regency inin academic year 2015/2016.This development research development research procedure using a modified Borg and Gall. Analysis of the data used for the development of descriptive analysis, feasibility analysis instrument based CBT evaluation score criteria, and the analysis of student learning outcomes using a t-test. The results of this study based on the results of descriptive analysis concluded that media expert validation evaluation obtained by percentage of 87.18 with very good criteria, subject matter experts with a percentage of 90.48 with the criteria of evaluation were excellent, expert evaluation evaluation obtained percentage of 75.00 with good criteria and by experts practitioners gained 87.50 percentage evaluation criteria very well. Based on the analysis testing the effectiveness of t = 5.631> table = 2.000, with significant value 0,000, which means an increase in the value of learning outcomes Archival experimental class is better than the control class value, 11.53 points. This suggests that learning evaluation instruments archival usingComputer Based Test (CBT) is effective in improving student learning outcomes compared archives without using instrumental evaluation of learning Computer Based Test (CBT). The conclusion of this study is the evaluation instrument of learning using Computer Based Test (CBT) fit for use and effectively to improve student learning outcomes. Keywords: Development, Learning Assessment instrument using Computer Based Test (CBT), learning outcomes. ABSTRAK               Penelitian ini untuk mengetahui kelayakan instrumen evaluasi pembelajaran menggunakan Computer Based Test (CBT) dan menguji keefektifan instrumenuntuk meningkatkan hasil belajar Kearsipan di SMK Kabupaten Karanganyar tahun pelajaran 2015/2016.Penelitian pengembanganini menggunakan prosedur penelitian pengembangan Borg and Gall yang dimodifikasi.Analisis data yang digunakan selama pengembangan adalah analisis deskriptif, analisis kelayakan instrumen evaluasi CBT berdasarkan skor kriteria, dan analisis hasil belajar siswa menggunakan t-test.Hasil penelitian iniberdasarkan hasil analisis deskriptif disimpulkan bahwa validasi ahli media diperoleh persentase evaluasi 87,18 dengan kriteria sangat baik, ahli materi dengan persentase evaluasi 90,48 dengan kriteria sangat baik, ahli evaluasi diperoleh presentase evaluasi 75,00 dengan kriteria baik dan oleh ahli praktisi diperoleh persentase evaluasi 87,50 dengan kriteria sangat baik. Berdasarkan hasil analisis uji keefektifan thitung = 5,631>ttabel= 2,000 dengan nilai signifikansi 0,000, yang berarti peningkatan nilai hasil belajar Kearsipan kelas eksperimen lebih baik dibandingkan dengan nilai kelas kontrol, sebesar 11,53 point. Hal ini menunjukkan bahwa instrumen evaluasi pembelajaran kearsipan menggunakan Computer Based Test (CBT) efektif meningkatkan hasil belajar kearsipan siswa dibandingkan tanpa menggunakan instrumen evaluasi pembelajaran Computer Based Test (CBT). Kesimpulan hasil penelitian ini adalah instrumen evaluasi pembelajaran menggunakan Computer Based Test (CBT) layak digunakan dan efektif untuk meningkatkan hasil belajar siswa, Kata kunci: pengembangan, instrumen evaluasi pembelajaran, Computer Based Test (CBT), hasil belajar.